Measuring Awareness, Readiness And Effectiveness Of Quality Ecosystem At Institut Kemahiran Mara - Syed Mohamed, Sharifah Syahira (2019)
MQS or Ecosystem Quality Standard is to create ecosystem quality that needs to be met at all Centres of MARA administration including corporate culture, environment conducive to include safety and health elements occupation, security of protection and generating ideas, creativity and innovation among employces. All MARA Administration Centres are required to carry out the MQS Certification. Application to obtain new MQS certification or MQS Certificate renewal should be submitted to the MQS Master Committee. Therefore, this project will be measuring awareness, readiness and effectiveness of quality ecosystem at Institut Kemahiran MARA Johor Bahru to fulfil the requirement of MQS certification of MARA. The objectives of this project including to determine the level of awareness and also to analyse the readiness of IKM Johor Bahru employees. The other objectives in this project is to provide an indicator the level of readiness verse the time taken needed to implement MARA Ecosystem Quality Standard (MQS) successfully. The methodology to achieve the all objectives is based on a survey study which is used open and closed ended questionnaire. The results in this project revealed that the questioned asked reach level of awareness at 0 and 1.0 have similar percentage with 39% for objective one. The results in objective two indicate that 63% of question asked reach level of readiness at 1.0 while the results in objective three shows that 76% is delay for level readiness versus time taken needed analysis. As a conclusion, the IKM’s Johor Bahru employee have a good level of readiness on MARA Ecosystem Quality Standard (MQS). However, they need to improved their awareness level on MARA Ecosystem Quality Standard (MQS). The other conclusion is the time taken to implement MQS will be reduced by increment numbers of employees who are ready.